Askans inverkan på beläggningstendensen i ett biobränsleeldat kraftvärmeverk och växtplatsens påverkan på askegenskaperna - Ericson, Sofia (2005)
This report was written by Sofia Ericson and describes the degree thesis with the title: "Connections between the growing site of bio fuel, the chemical composition of bio fuel ash and the deposit growth in a bio fuel fired boiler." The purpose of this degree thesis was to avoid melted deposit growth in the bio fuel fired boiler at ENA Kraft in Enköping.